Morphometrics and genetics variations of mullets (Pisces: Mugillidae) from Aceh waters. Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Yulianto D, Batubara IIAS, Nur FM, Rizal S, Siti-Azizah MN, Muchlisin ZA. 2020. Morphometrics and genetics variations of mullets (Pisces: Mugilidae) from Aceh waters, Indonesia. Biodiversitas 21: 3422-3430.  Mullets are one of the commercial groups of coastal fish living in Aceh waters, in Indonesia. Presently, there is limited information on the bioecology, especially on the genetics and morphometrics of these fishes. Therefore, the objective of this study is to examine the morphology and genetic variations of Liza macrolepis, Liza tade, and Moolgarda engeli mullets. This study was conducted from January 2018 to July 2019 in four locations along the northern and eastern coasts of Aceh.  Data were obtained by measuring the morphometrics of a total of 180 samples of the species in equal ratios. The data were analyzed using the ANOVA and Discriminate function analysis (DFA). The ANOVA test showed that at least 75% of characters are not significantly different among the mullets. Meanwhile, the discriminant function analysis produces the two functions with Eigenvalue of 0.627 and 0.107 with 85.5% and 17.2% total variants, respectively.  Function 1 discriminates the mullet samples into two groups; the first was L. tade, and the second belonged to L. macrolepis and M. engeli. In addition, a total of 18 samples of mullets consisting of 8 samples of the L. macrolepis, 2 samples of the L tade, and 8 samples of the M. engeli were successfully amplified from the 5' region of the mitochondrial cytochrome oxidase subunit I (COX1) gene using a pair of primers (Fish F1 and Fish R1). Furthermore, a total of 7 haplotype sequences were produced from the ingroup where L. tade has one haplotype, L. macrolepis and M. engeli had three haplotypes, respectively. The genetic distance analysis showed that the interspecific distance was 0.38% and intraspecific was 8.2%. Therefore, the COI gene successfully discriminated against the mullet into three valid species.
Keywords: COX1gene, Discriminant Function Analysis, Liza macrolepis, Liza tade, Moolgarda engeli